Arterial stiffness in normal pregnancy at 11–13 weeks of gestation and risk of late-onset hypertensive disorders of pregnancy. Issue 5 (May 2019) - Marozio, Luca; Chiarle, Giulia; Filippini, Claudia; Challancin, Stephanie; Tancredi, Annalisa; Viora, Elsa; Benedetto, Chiara
Abstract : Objective: We evaluated the possible correlation between pulse wave analysis (PWA) parameters measured during the first trimester of pregnancy in normotensive, low-risk women, and the development of hypertensive disorders later in pregnancy. Our hypothesis was that a still asymptomatic increase in arterial stiffness may potentially precede the onset of overt hypertension in pregnancy and that PWA could detect it. Methods: The study population ( n = 1648) was recruited at the time of prenatal screening for chromosomal abnormalities (11 +0 –12 +6 weeks of gestation). The radial pressure waveform was obtained with an applanation tonometer (Sphygmocor, Atcor Medical, West Ryde, Australia) on pregnant women in recumbent position. Arterial stiffness was evaluated using arterial PWA. The aortic systolic pressure (aSp), aortic diastolic pressure, and aortic mean pressure, the aortic pulse pressure, the augmentation pressure, and the augmentation index were calculated. The main outcome measure was the development of hypertensive disorders later in pregnancy. Results: The values of aSp ( P < 0.0001), aortic diastolic pressure ( P < 0.0001), aortic mean pressure ( P < 0.0001), aortic pulse pressure ( P = 0.0140), and augmentation index-75 ( P < 0.0001) measured in the first trimester of pregnancy were significantly higher in the women who later developed hypertensive disorders of pregnancy than in those who remained normotensive. The aSp (sensitivity 72.6%; specificity 59.6%) was found to be the best predictor for the later development of hypertension. Conclusion: In normotensive, low-risk pregnant women, PWA may be useful for the early detection of risk for the development of hypertensive disorders of pregnancy.